Comprehensive utilisation of sorghum (Sorghum bicolor) in the food industry and its nutritional properties: A review - Tan, Daphne; Alfonsus, Angelica Putri; Tinardi, Cicilia; Nathania, Angeline; Vienna, Shane; Astina, Junaida; Fugaha, Daniel Ryan (Indonesian Journal of Life Sciences, 2024)
Sorghum is one of the potential local carbohydrate sources in Indonesia. It is rich in nutrients. However, the utilisation of sorghum as staple food in Indonesia is lacking due to limited information on the cultivation, processing, and nutritional properties of sorghum. Hence, it is crucial to encourage the consumption and utilisation of sorghum to promote food diversification and sustainability. Sorghum has a distinct classification depending on its variety and each component has its own discrete functionality, with red sorghum being the most utilised varieties in Indonesia. Sorghum is high in fibre and protein (6.7 g/100 g and 1.6 g/100 g, respectively) and, therefore, contributes to the low glycemic index of sorghum. Several health benefits are possessed by sorghum, including anti-diabetic and antihypertensive properties. Moreover, the gluten-free nature of sorghum makes it suitable for people suffering from celiac disease. Utilisation of sorghum and its processing were also discussed comprehensively in this review, including utilisation of sorghum as the rice substitute, gluten-free flour, syrup, sweet soy sauce, and sorghum as plant-based milk. As such, the implementation of sorghum in Indonesia should be further optimised and promoted due to their beneficial properties as well as diverse utilisation.